Direct-to-Implant Breast Reconstruction without the Use of an Acellular Dermal Matrix Is Cost Effective and Oncologically Safe. Issue 4 (April 2017) - Serrurier, L. Charles. J.; Rayne, Sarah; Venter, Marisse; Benn, Carol-Ann
Abstract : Background: Direct-to-implant breast reconstruction is a predictable, reliable, and cost-effective reconstruction. Most units performing direct-to-implant reconstructions recommend the use of an acellular dermal matrix or a mesh to reinforce the lower pole of the breast reconstruction. Methods: Two hundred seventy-two consecutive patients with 488 immediate direct-to-implant breast reconstructions performed in a 34-month period are included in this group. Mean follow-up of this group is 35 months. Results: Four hundred eight reconstructions were performed through a lazy-S mastectomy, and 80 were performed through a Wise pattern mastectomy. Two local recurrences occurred. Minor complications accounted for 5.5 percent ( n = 27): seromas, 3.4 percent ( n = 17); wound healing problems, 0.6 percent ( n = 3); and grade 2 capsular contracture, 1.4 percent ( n = 7). Major complications accounted for 4.3 percent ( n = 21): infection, 0.8 percent ( n = 4); prosthetic loss, 0.4 percent ( n = 2); hematoma, 0.4 percent ( n = 2); and wounds requiring débridement, 2 percent ( n = 10). The additional cost of acellular dermal matrix is dependent on manufacturer and size, but increases the cost of the procedure by 35.5 to 47.7 percent. Conclusions: This reconstruction method compares very favorably with published data from other units as far as early and late complications and cosmetic outcome are concerned. It has a complication rate similar to that of reconstructions using an acellular dermal matrix and is more cost effective. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.